Insuring the future of farmers under climate change: Panel Discussion - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Recorded live in London, 28 January 2015. Learn more about index insurance: https://ccafs.cgiar.org/weather-index-based-insurance Speakers: Jon Hellin, CIMMYT Pramod Aggarwal, CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) Ms. Clare Shakya, DFID Mr. Bashiru Martins, Agricultural Insurance Corporation of Nigeria Mr. Joseph Plappallil, Agriculture Insurance Company of India Mr. Mario Wilhelm, Vice President, Global Partnerships, Swiss Re Corporate Solutions Dr. Chirantan Bannerjee, Deutsche Gesellschaft fÁ¼r internationale Zusammenarbeit (GIZ) Dr. Débísí Á€rÁ bÁ , Office of the Honourable Minister of Agriculture and Rural Development, Nigeria Moderator: Julian Roberts, Willis